1983
DOI: 10.1111/j.1365-2133.1983.tb00547.x
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of primary irritant hand dermatitis

Abstract: Four hundred and sixty-two patients suffering from primary irritant hand dermatitis were sent postal questionnaires after 1-16 years regarding the outcome of their dermatitis. Two hundred and thirteen patients replied (a compliance rate of 46%). Of the 213 replies 188 were accepted for analysis, of whom only 58 (30.8%) had complete remission of their dermatitis, whilst 130 patients (69.2%) had continuous, or intermittent disease. Of sixty-four patients who changed their occupation only twenty-one (32.8%) had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…reported that 89% of 62 workers who remained at their jobs continued to be affected while 69% of 58 workers who left their job because of the skin disease remained affected. Keczkes et al 22 . found no difference in clearance of dermatitis between 64 workers with ICD who left their jobs and 124 who stayed.…”
Section: Discussionmentioning
confidence: 95%
“…reported that 89% of 62 workers who remained at their jobs continued to be affected while 69% of 58 workers who left their job because of the skin disease remained affected. Keczkes et al 22 . found no difference in clearance of dermatitis between 64 workers with ICD who left their jobs and 124 who stayed.…”
Section: Discussionmentioning
confidence: 95%
“…Those who were advised to change jobs and followed the advice had a better outcome, suggesting that there may be a subgroup of workers with OSD for whom a job change is clearly beneficial. There is conflicting information in the literature regarding the association between change in job and status of dermatitis, with some groups reporting less dermatitis in workers who have changed jobs [Breit and Turk, 1976;Johnson and Wilson, 1971;Wall and Gebauer, 19911, while others felt it to be of no benefit [Keczkes et al, 1983;Johnson and Wilson, 1971;Fregert, 19751, and others reported mixed results [Hellier, 19581. The results of all these investigations are difficult to interpret because they are observational studies, not experimental interventions.…”
Section: Discussionmentioning
confidence: 96%
“…Disease that is persistent has not only clinical ramifications, but also impacts on employment. A number of studies that have examined the prognosis of contact dermatitis have assessed employment outcome and also the effects of changing jobs [Breit and Turk, 1976;Squire et al, 1950;Lammintausta et al, 1982;Burrows, 1972;Keczkes et al, 1983;Johnson and Wilson, 1971;Hellier, 1958;Fregert, 1975;Meding and Swanbeck, 1990;Christensen, 1982;Skog and Tottie 19611. While some authors suggest that a change in employment does not significantly improve outcome and should not be suggested in most instances, there are still instances in clinical practice where this was done with advantageous results. Nonethe-less, there is relatively little information available to assist the clinician or workers' compensation authorities in determining whether the chronic state will persist and what job changes might be appropriate to minimize or eliminate continuing skin disease.…”
Section: Introductionmentioning
confidence: 98%
“…85,93 The majority of studies assessing the role of change in occupation among workers with OCD have not found the prognosis to be improved. 85,[93][94][95][96][97][98][99] Many workers can continue to work despite ongoing OCD. 85,94,[100][101][102][103][104] Although the prognosis of OCD may be guarded, if the affected worker can continue to work, he or she may have a better social prognosis despite the ongoing presence of OCD.…”
Section: Prognosis Of Ocdmentioning
confidence: 97%